Pengaruh Kecerdasan Emosional, Budaya Organisasi, dan Adaptabilitas Karir Terhadap Kinerja Karyawan di Amira Aesthetic Clinic - Rhamadanti, Revina; Arifiansyah, Rully (Human Capital Development, 2024)
The study explores the role of emotional intelligence, organizational culture, and career adaptability in improving employee performance. The survey was conducted on 120 employees in six branches of Amira Aesthetic Clinic. Sampling is carried out purposively by prioritizing employees who already have at least 3 months of work experience. Employees who already have at least 3 months of work experience. Then, hypothesis analysis will be performed using multiple linear regression with the help of SPSS software version 26. The results showed that organizational culture had the most dominant significant impact on improving employee performance, along with other factors such as emotional intelligence and career adaptability. Verbs : emotional intelligence, organizational culture, career adaptability, performance